Corporate Governance and Firm Performance in State-Owned Enterprises (SOEs) in Zambia: A Systematic Review - Bryson Mumba; Eustarckio Kazonga (Journal of Corporate Governance Research, 2024)
The research systematically documented and described the corporate governance practices and financial performance in State-Owned Enterprises (SOEs) in Zambia from 2006 to 2017. The research design that was adopted was the descriptive research design to systematically describe the corporate governance practices and financial performance of SOEs in Zambia. The corporate governance attributes for SOEs such as board size, board appointing authorities and board membership have been found to be prescribed by a diversity of Acts of Parliament for different SOEs. This finding suggests that the governance of these entities could be a challenge insofar as the uniformity of the legal framework for the governance of the entities was concerned. In addition to this, board membership which are designated by specific government positions rather than merit based, compromises board effectiveness. The study has further shown that failure to produce and publish, for public scrutiny, audited financial statements on a timely basis leads to lack of transparency and accountability. The financial performance has been found to have been poor as the SOEs on average produced negative returns on total assets and the SOEs were highly geared based on operating gearing and financing gearing. Lastly, financial performance of SOEs and the corporate governance practices differed significantly across different industries under which the SOEs operated.